Prescribed doses of inhaled steroids in Dutch children: too little or too much, for too short a time - Schirm, Eric (Blackwell Science Inc, 2006)
AIMS: To investigate the dosage and duration of inhaled steroids prescribed to children and to compare the prescribed doses with recommended doses for the treatment of asthma in children. METHODS: For 2514 Dutch children aged 0–12 years who had used inhaled steroids in 2002, pharmacy dispensing data were obtained from the InterAction database, type of steroid (beclomethason, budesonide, fluticasone) and type of user (first time or existing) and the average prescribed doses according to age were determined and compared with the doses as recommended in the national Dutch Nederlands Huisartsen Genootschap (NHG) guideline. Furthermore, for all first-time users the duration of therapy with inhaled steroids was determined using a Kaplan–Meier analysis. RESULTS: The major findings were that: (i) overall 43% of children starting inhaled steroids were prescribed doses that are half the recommended dose or less; (ii) overall 8% of the children starting inhaled steroids were prescribed doses that were twice the recommended dose or more, up to 50% in the 12-year-olds fluticasone group; and (iii) only 8% of the children who started with inhaled steroids used them continuously for a full year. CONCLUSIONS: Doses of inhaled steroids for many children deviate from those recommended, with lower doses more frequently occurring than higher doses. Less than 10% of the children receive prescriptions for a prolonged period of time.